2014
DOI: 10.3390/md12052922
|View full text |Cite
|
Sign up to set email alerts
|

Echinochrome A Protects Mitochondrial Function in Cardiomyocytes against Cardiotoxic Drugs

Abstract: Echinochrome A (Ech A) is a naphthoquinoid pigment from sea urchins that possesses antioxidant, antimicrobial, anti-inflammatory and chelating abilities. Although Ech A is the active substance in the ophthalmic and cardiac drug Histochrome®, its underlying cardioprotective mechanisms are not well understood. In this study, we investigated the protective role of Ech A against toxic agents that induce death of rat cardiac myoblast H9c2 cells and isolated rat cardiomyocytes. We found that the cardiotoxic agents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 31 publications
4
77
0
2
Order By: Relevance
“…[8] Echinochrome A protected mitochondrial functions from cardiotoxic agents such as doxorubicin, sodium nitroprusside and tert-butyl hydroperoxide. [9] Echinochrome A treatment enhanced the oxygen consumption rate and the mitochondrial ATP level in rat cardiomyoblast cells and up-regulated the biogenesis of transcription genes. [10] Egyptian scientists demonstrated the potential of echinochrome A in the treatment of rats with experimental type 1 and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[8] Echinochrome A protected mitochondrial functions from cardiotoxic agents such as doxorubicin, sodium nitroprusside and tert-butyl hydroperoxide. [9] Echinochrome A treatment enhanced the oxygen consumption rate and the mitochondrial ATP level in rat cardiomyoblast cells and up-regulated the biogenesis of transcription genes. [10] Egyptian scientists demonstrated the potential of echinochrome A in the treatment of rats with experimental type 1 and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 96%
“…The most well‐known sea urchin pigment, echinochrome A, also showed antiallergic activity . Echinochrome A protected mitochondrial functions from cardiotoxic agents such as doxorubicin, sodium nitroprusside and tert ‐butyl hydroperoxide . Echinochrome A treatment enhanced the oxygen consumption rate and the mitochondrial ATP level in rat cardiomyoblast cells and up‐regulated the biogenesis of transcription genes .…”
Section: Introductionmentioning
confidence: 99%
“…One form of Histochrome is used in the treatment of ocular diseases [179] and another form of Histochrome is used for preventing reperfusion damage during myocardial infarction [177]. In order to understand the cardioprotective mechanisms of echinochrome A, Jeong et al [180] found that cardiotoxic agents caused mitochondrial dysfunction as a result of increased ROS level and decreased mitochondrial membrane potential were inhibited with PHNQ.…”
Section: Other Bioactivitiesmentioning
confidence: 99%
“…Echinochrome and spinochromes from sea urchins have been shown to possess antimicrobial, anti-inflammatory and anti-allergenic activities (Table 13) [174][175][176][177][178][179]. Echinochrome A is the active substance in the drug Histochrome [178].…”
Section: Other Bioactivitiesmentioning
confidence: 99%
“…Polyhydroxylated naphthoquinone pigments from the shells of purple sea urchin ( Anthocidaris crassispina ) possessed a strong antiradical activity against 1,1-diphenyl-2-picrylhydrazyl (DPPH), superoxide radical anion, and hydrogen peroxide [6]. For example, polyhydroxylated 1,4-naphthoquinone exhibited dose-dependent antioxidant activities on DPPH radicals [7,8] and inhibited the model of ocular allergic inflammation surpassing the reference drug olopatadine [9]; 6-ethyl-2,3,5,7,8-pentahydroxy-1,4-naphthoquinone (Echinochrome A) existing in sea urchin shells and spines could be used as the auxiliary agent for reducing cardio toxic agent-induced damage [10]. …”
Section: Introductionmentioning
confidence: 99%